The educational implications of the folkways, mores and religious beliefs of the Gadangs - Gamboa, Enriqueta Tiongson 1931- (1960)
The aims of this study are (1) to know the Gadang's customs and traditions: what type of home life he has, what his folkways, mores and religious beliefs are, and (2) to determine what his general attitudes are toward formal education as influenced by his ways of life and (3) to identify the educational implications of these findings.
Bibliography: l. 195-198.
Mimeographed
Thesis (M.Ed.)--University of the Philippines, 1960
Vita
Keywords: Gaddangs -- Social life & customs